인간-생성형 인공지능의 협력 - 예비 종교교사의 학습 경험 탐색 - 김효숙(KIM Hyo-Sook) (Changsin nondan, 2024)
디지털 심화 시대에 접어들면서 교육 분야에서 인공지능(AI)의 활용이 확대되고 있으며, 특히 생성형 AI가 학습자의 인지적 파트너로서 협력할 가능성에 대한 논의가 활발해지고 있다. 이러한 흐름을 고려하여 본 연구는 예비 종교교사와 생성형 AI의 협력을 지원하는 학습환경을 설계하고, 예비 종교교사의 디지털 리터러시 및 생성형 AI 수용도에 미치는 영향과 협력 경험을 분석하여 생성형 AI의 교육적 의미와 역할을 탐색하고자 하였다. 연구 결과, 생성형 AI와의 협력은 예비 종교교사의 디지털 리터러시 역량 향상에 긍정적인 영향을 미쳤으며, 생성형 AI의 수용도 또한 증가한 것으로 나타났다. 이는 생성형 AI가 학습자의 파트너로서 효과적으로 기능할 수 있음을 시사한다. 예비 종교교사의 협력 경험을 테크놀로지 교수내용지식(TPACK) 프레임워크로 분석한 결과, 테크놀로지 지식(TK)과 테크놀로지 교수지식(TPK)에서 뚜렷한 향상이 확인되었으나 테크놀로지 교수내용지식(TPACK)은 상대적으로 낮은 향상을 보였다. 이러한 연구 결과는 예비 종교교사 교육 시 테크놀로지와 교수법, 교육 내용이 보다 체계적이고 통합적으로 이해, 적용될 필요가 있음을 시사한다. 본 연구는 예비 종교교사와 생성형 AI의 협력에 대한 예비적 연구이나 예비 종교교사의 생성형 AI와의 협력 경험이 디지털·AI 소양을 강화할 수 있음을 실증적으로 논의한다는 점에서 의의를 갖는다. In an era of increasing digital sophistication, the utilization of Artificial Intelligence (AI) in education is expanding. In particular, there is growing discussion about the potential of generative AI to collaborate with learners as a cognitive partner. In light of this trend, this study aimed to design a learning environment that supports collaboration between pre-service religious education teachers and generative AI. The impact of this collaboration on the pre-service teachers’ digital literacy and acceptance of generative AI was investigated, and their collaborative experiences were analyzed to explore the educational implications and role of generative AI. The results revealed that collaboration with generative AI had a positive influence on enhancing the digital literacy competencies of pre-service religious education teachers, and their acceptance of generative AI also increased. This suggests that generative AI can function effectively as a partner for learners. An analysis of the pre-service teachers’ collaborative experiences using the Technological Pedagogical Content Knowledge (TPACK) framework demonstrated significant improvements in Technological Knowledge (TK) and Technological Pedagogical Knowledge (TPK), while Technological Pedagogical Content Knowledge (TPACK) showed relatively lower improvement. These findings suggest that pre-service religious education teacher training programs need to facilitate a more systematic and integrated understanding and application of technology, pedagogy, and content knowledge. This study is a preliminary investigation into the collaboration between pre-service religious educators and generative AI. However, it holds significance in that it empirically discusses how pre-service religious educators’ experiences of collaborating with generative AI can enhance their digital and AI literacy. KCI Citation Count: 0